2016
DOI: 10.21082/ijas.v5n1.2004.p20-31
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rice Cultivars on Methane Emission From Irrigated Rice Field

Abstract: Rice plants have been reported to affect methane (CH4) emission from rice fields. The objectives of this study were to determine the effect of rice cultivars on CH4 emission from flooded rice and to develop crop management strategies with low emitting rice cultivars while sustaining high yield. The four rice cultivars studied were Memberamo, Cisadane, IR64, and Way Apoburu. The CH4 emissions were determined in the wet season of 2001/2002 (November-February) using an automated closed chamber technique in an irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Many studies have reported that there are substantial differences in the rates of CH 4 emission from different rice cultivars [40][41][42]. The effect of rice cultivars on methane emissions is mostly related to rice growth performance, i.e., the number of plant tillers, and the plant above-and belowground biomass affect CH 4 transport potential and root exudation [40][41][42]. There were no significant differences in cumulative CH 4 emissions between the tested rice varieties in both rice seasons (Figure 5a,b).…”
Section: Methane Emission In Relation To Different Awd Managementmentioning
confidence: 99%
“…Many studies have reported that there are substantial differences in the rates of CH 4 emission from different rice cultivars [40][41][42]. The effect of rice cultivars on methane emissions is mostly related to rice growth performance, i.e., the number of plant tillers, and the plant above-and belowground biomass affect CH 4 transport potential and root exudation [40][41][42]. There were no significant differences in cumulative CH 4 emissions between the tested rice varieties in both rice seasons (Figure 5a,b).…”
Section: Methane Emission In Relation To Different Awd Managementmentioning
confidence: 99%
“…Many findings on CH 4 and N 2 O emission from conventional paddy fields have been reported since the early 1990s. Among others are: under intermittent irrigation, CH 4 and N 2 O emissions have been seen to vary depending on the paddy varieties planted (Husin et al, 1995;Setyanto et al, 2004) and on the fertilizer applications (Cai et al, 1997;Nishimura et al, 2004). CH 4 emission in drained paddy fields is temperature-dependent, and accordingly varies diurnally with its maximum value occurring in the afternoon (Miyata et al, 2000;Purkait et al, 2007).…”
mentioning
confidence: 99%
“…Methane produced in flooded rice soils is emitted to the atmosphere by molecular diffusion, ebullition or plant-mediated transport. Approximately 80–90% of the total CH 4 flux is emitted to the atmosphere from the rhizosphere via the rice plant [ 17 ]. An increase in plant biomass [ 18 ] and tiller number [ 19 ] enhanced CH 4 oxidization activity by enlarging the volume of aerenchyma and enhancing O 2 transport from the atmosphere to the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%